Topographic attributes and ecological indicator values in assessing the ground-floor vegetation patterns - Czarnecka, Bożenna; Rysiak, Anna; Chabudziński, Łukasz (Biodiversity: Research and Conservation, 2017)
The GIS and DEM became useful tools for the detection of patterns of species with different habitat requirements. The species number correlated positively with the total and flat area of a section and the TWI, while the denivelation, mean slope and upslope area had a reverse vector. Among the most frequent and abundant herb species, we found several spatial patterns of distribution, namely those of: Maianthemum bifolium, Carex remota, C. acutiformis, Filipendula ulmaria, Dryopteris filixmas, and Urtica dioica. The rarest species represented Ajuga genevensis, Scorzonera humilis, and Stachys palustris patterns.